Association of lung immune prognostic index with survival outcome in advanced thymic carcinoma patients treated with palliative intent chemotherapy - Taisuke Araki; Kazunari Tateishi; Masamichi Komatsu; Kei Sonehara; Shintaro Kanda; Masayuki Hanaoka; Tomonobu Koizumi (Thoracic Cancer, 2022)
Abstract Background The prognostic implications of palliative chemotherapy for advanced or recurrent thymic carcinomas require full elucidation. The lung immune prognostic index (LIPI) is a novel prognostic index whose effectiveness has recently been reported in lung cancer patients. This study aimed to evaluate the clinical value of the LIPI in advanced or recurrent thymic carcinoma patients. Methods We retrospectively analyzed 41 advanced or recurrent thymic carcinoma patients undergoing palliative chemotherapy between January 2001 and December 2020. Survival‐time analysis was conducted using the Kaplan–Meier method and log‐rank test. Multivariate analysis using the Cox proportional hazards model was performed to investigate the predictive and/or prognostic value of the LIPI. Results Median progression‐free survival (PFS) for first‐line chemotherapy and overall survival (OS) were significantly longer in the good‐LIPI group (LIPI: 0) than in the intermediate/poor‐LIPI group (LIPI: 1 or 2) (PFS: 13.4 vs. 6.8 months, p = 0.025; OS: 48.2 vs. 28.9 months, p = 0.00506). Multivariate analysis revealed that intermediate/poor LIPI was the adverse prognostic factor for PFS. With regard to OS, serum albumin <3.5 g/dl and an intermediate/poor LIPI were identified as independent adverse prognostic factors. Conclusions Our study indicates that the LIPI is a potential prognostic marker in patients with advanced or recurrent thymic carcinoma undergoing palliative chemotherapy.